Rewrite in Standard Form y-4=3(x-(-7))

Math
y-4=3(x-(-7))
The standard form of a linear equation is Ax+By=C.
Simplify 3(x-(-7)).
Tap for more steps…
Multiply -1 by -7.
y-4=3(x+7)
Apply the distributive property.
y-4=3x+3⋅7
Multiply 3 by 7.
y-4=3x+21
y-4=3x+21
Rewrite the equation with the sides flipped.
3x+21=y-4
Move all terms containing variables to the left side of the equation.
Tap for more steps…
Subtract y from both sides of the equation.
3x+21-y=-4
Move 21.
3x-y+21=-4
3x-y+21=-4
Move all terms not containing a variable to the right side of the equation.
Tap for more steps…
Subtract 21 from both sides of the equation.
3x-y=-4-21
Subtract 21 from -4.
3x-y=-25
3x-y=-25
Rewrite in Standard Form y-4=3(x-(-7))

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top